Citizen-led Grievance Redress for Road Construction and Urban Infrastructure Upgrades : Experiences from Two Projects in Rwanda - World Bank (Washington, DC : World Bank, 2022)
This case study examines the grievance redress mechanisms (GRMs) put in place for two World Bank financed projects in the Republic of Rwanda: the Feeder Roads Development Project (FRDP) and the Rwanda Urban Development Project (RUDP). Based on consultations and interviews with key informants, such as project-affected parties who submitted complaints to one of the project-level GRMs and members of grievance redress committees, as well as on desk research and data provided by social and safeguards officers of project implementation units and World Bank task teams, section 1 provides an overview of both projects; section 2 describes the social accountability framework in which they were implemented; section 3 explores the way grievances were taken up, investigated, and resolved; section 4 considers key grievance data; section 5 assesses the main strengths of the GRMs; section 6 investigates areas for improvement; and section 7 outlines a few conclusions and recommendations for practitioners.